2022
DOI: 10.1159/000528516
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Atrial Fibrillation after Ischemic Stroke: Clinical, Genetics, and Electrocardiogram Modelling

Abstract: Introduction: Detection of atrial fibrillation (AF) is challenging in patients after ischemic stroke due to its paroxysmal nature. We aim to determine the utility of a combined clinical, electrocardiographic and genetic variables model to predict AF in a post-stroke population. Materials and Methods: We performed a cohort study at a single comprehensive stroke centre from 09/11/2009 to 31/10/2017. All patients recruited were diagnosed with acute ischemic stroke or transient ischemic attacks. Electrocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Interestingly, our study revealed a noteworthy finding: the cohort of stroke patients with hypertension exhibited a heightened likelihood of AF detection compared to their counterparts without hypertension. This finding contrasts with the observations in the study by Poh et al [24]. Hence, further well-designed investigations are warranted to precisely ascertain the relationship between hypertension and AF within the stroke population.…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly, our study revealed a noteworthy finding: the cohort of stroke patients with hypertension exhibited a heightened likelihood of AF detection compared to their counterparts without hypertension. This finding contrasts with the observations in the study by Poh et al [24]. Hence, further well-designed investigations are warranted to precisely ascertain the relationship between hypertension and AF within the stroke population.…”
Section: Discussioncontrasting
confidence: 89%
“…Tachycardia-associated arrhythmias, especially AF, are more frequent than bradycardias [15,26]. The incidence of AF following AIS is approximately 5-24% [21][22][23][24]. Consistent with the above-mentioned results, the incidence of AF detected after stroke (AFDAS) was higher in strokes involving the right insula (39%) than in strokes involving the left insula (4%) [61].…”
Section: Electrocardiographic Changes and Cardiac Arrhythmiasmentioning
confidence: 58%
“…Dynamic analysis of the RR interval performed in the hyperacute phase of AIS can help identify high-risk paroxysmal AF episodes [110]. Several predictive models have been developed for AFDAS [23,111]. Further, a study established a multimodal approach incorporating imaging, ECG, and original biomarkers [112].…”
Section: Early Prediction and Identification Of Shsmentioning
confidence: 99%
“…Monitoring PWTF provides a dynamic assessment of these changes, aiding in the early detection of atrial remodelling and potential AF development. 28,29 Understanding the relationship between PW parameters and AF has important clinical implications. These electrocardiographic indices, which can be obtained from routine evaluations after PFO closure, provide a non-invasive method for identifying individuals at risk of AF.…”
Section: Discussionmentioning
confidence: 99%